Effects of zinc oxide nanoparticles (ZnO NPs) on the biology of Galleria mellonella L. (Lepidoptera: Pyralidae) - NURULLAHOĞLU, ZAHİDE ULYA (My University, 2022)
Background: Because of its ability to absorb UV radiation and possess catalytic, antibacterial, and semiconducting properties, zinc oxide nanoparticles (ZnO NPs) are increasingly being used in consumer goods. Because nanoparticles are used so often, accurate methods for determining any associated toxicity are crucial. The greater wax moth, Galleria mellonella (L.) (Lepidoptera: Pyralidae) is a suitable experimental model organism due to immune defense of the larvae is very strong. Also, larvae are a good model for carrying out toxicity studies. In this study, to determine the effects of zinc oxide NPs (ZnO NPs) on the biology (larval development time, the weight of the last stage larvae, the pupal development time, the pupal weight, the eclosion rate, the maturation period, the adult weights, the adult longevity, and the percentage of adults) of G. mellonella, zinc oxide NPs were added to the larvae diet (honeycomb) at different doses (100, 500, 1000, 3000, and 5000 ppm). Results: Results showed that pupal weights significantly decreased at 1000, 3000, and 5000 ppm doses of zinc oxide NPs when compared with control. Adult weight increased at 100 ppm zinc oxide NPs and the adult longevity of G. mellonella in the group exposed to 5000 ppm zinc oxide NP was longer than the control group. Finally, total male longevity extended in 500, 1000, 3000, and 5000 ppm zinc oxide NPs groups when compared to the control group. Conclusions: The findings of this study contribute to evidence that the negative effects of ZnO NPs on biological properties on G. mellonella. In addition, the study reveals the adverse effects of zinc oxide NPs on a model experimental organism and provides an idea for researchers working on this subject in terms of new studies that can be done in future.
Keywords: Tıp; Tıbbi Biyoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Medical Biology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; BİYOLOJİ; Biyoloji ve Biyokimya; Yaşam Bilimleri (LIFE); BIOLOGY; BIOLOGY & BIOCHEMISTRY; Life Sciences (LIFE); Biyokimya (tıbbi); Biochemistry (medical); Biology; Galleria mellonella; Nanoparticle; Toxicity; Zinc oxide; GIBBERELLIC-ACID; NANO ZNO; HYMENOPTERA; HETEROPTERA; HEMOCYTES; MEDICINE; BEHAVIOR; STRESS; INSECT; GROWTH; Biology; Galleria mellonella; Nanoparticle; Toxicity; Zinc oxide